ANALISIS PENGARUH KONFLIK PERAN DAN AMBIGUITAS PERAN TERHADAP KOMITMEN ORGANISASI MELALUI STRES KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PT. Telekomunikasi Indonesia, Tbk. Witel Semarang) - Silvia, Cindy; Yuniawan, Ahyar (Diponegoro Journal of Management, 2017)
Role conflict and role ambiguity that experienced by employees on a company can causing job stress. Job stress experienced by employee can directly effect the high and low of employees organizational commitment. The aim of this research was to examine and analyze the influence of role conflict to job stress, the influence of role ambiguity to job stress, the influence of job stress to organizational commitment, the influence of role conflict to organizational commitment through job stress as intervening variable and the influence of role ambiguity to organizational commitment through job stress as intervening variable.The population in this research was employees at PT. Telekomunikasi Indonesia, Tbk. Witel Semarang with total amount of 170 employees by taking the research sample as much as 90 employees using quota sampling technique. Data would be analyzed by using multiple linear regression analysis. The data testing technique used path analysis or path analysis,  which  the  path  analysis  includes:  test  validity,  reliability  test,  classical assumption test, T test, F test, coefficient determination test and test sobel to test the mediation effect.Based on the result of this research, the researcher concluded that role conflict and role  ambiguity  had  positive  and  significant  influence  to  job  stress.  Job  stress  had  a negative  and  significant  effect  on  organizational  commitment.  Role  conflict  had  no negative and significant effect on organizational commitment mediated by job stress, whereas   role   ambiguity  had   a   negative   and   significant   effect   on   organizational commitment that was mediated by job stress.